COVID-19 impact on thrombotic complications in cancer patients - A. V. Vorobev; S. E. Einullaeva; A. S. Borodulin; M. A. Shikina; S. A. Aliev; A. G. Solopova; V. N. Galkin; A. E. Ivanov; V. O. Bitsadze; J. Kh. Khizroeva; D. V. Blinov; J.-C. Gris; et al. (IRBIS LLC, 2024)
Aim: to study the features of thrombotic complications in cancer patients during COVID-19 infection, and identify the most significant diagnostic and prognostic criteria.Materials and Methods. Within the framework of cohort non-randomized study, there were analyzed the course of coronavirus infection in 72 hospitalized patients with uterine cancer (n = 22), cervical cancer (n = 19), ovarian cancer (n = 24) as well as vaginal and vulvar cancer (n = 7). All patients hospitalized for COVID-19 were examined and treated in accordance with the Interim guidelines "Prevention, diagnosis and treatment of novel coronavirus infection (COVID-19)" effective at the time of therapy. Additionally, on days 3-7 after hospitalization, a blood test was performed once to determine the level of metalloproteinase ADAMTS-13 (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13), ADAMTS-13 activity, ADAMTS-13 inhibitor and von Willebrand factor (vWF) level.Results. It was shown that the average age of the patients was 56.96 ± 7.55 years, the length of hospitalization ranged from 7 to 19 (13.0 ± 3.79) days. The disease severity was assessed by the degree of lung tissue damage based on computed tomography (CT), respiratory failure and development of systemic inflammatory response syndrome (SIRS). During hospitalization, CT-2 was detected in 46 (63.9 %) patients, CT-3 - in 26 (36.1 %) patients; 37 (51.4 %) patients were transferred to the intensive care unit (ICU). Clinically significant deep vein thrombosis (DVT) was diagnosed in 9 (12.5 %) patients, and pulmonary embolism (PE) - in 4 (5.6 %) patients. Of these, 6 cases of DVT and 3 cases of PE were fatal. A total of 14 (19.44 %) patients deceased due to developing acute cardiopulmonary failure. A vWF/ADAMTS-13 ratio greater than 2.1 was found in all ICU patients. Despite anticoagulant therapy, patients with DVT and PE had this ratio higher than 3.3 (4.00 ± 0.48), whereas in all 14 deceased patients it exceeded 2.98.Conclusion. Venous thromboembolism, including PE and DVT, has been identified as а serious complication of COVID-19. An opportunity to predict them early is of special importance because they may lead to serious complications such as disseminated intravascular coagulation, SIRS, cardiopulmonary failure, and death. In patients suffering from cancer infected with COVID-19, not only a decline in ADAMTS-13 activity and level was detected, but also a parallel increase in vWF level. A vWF/ADAMTS-13 ratio may be an early indicator of COVID-19 severity in such patients: a vWF/ADAMTS-13 ratio exceeding 2.1 was common for all ICU patients. Hence, it evidences about a potential for using this parameter to early identify such risk patients who may require more intensive care and medical intervention.